2023
DOI: 10.1007/s00239-023-10118-z
|View full text |Cite
|
Sign up to set email alerts
|

Decay of Skin-Specific Gene Modules in Pangolins

Abstract: The mammalian skin exhibits a rich spectrum of evolutionary adaptations. The pilosebaceous unit, composed of the hair shaft, follicle, and the sebaceous gland, is the most striking synapomorphy. The evolutionary diversification of mammals across different ecological niches was paralleled by the appearance of an ample variety of skin modifications. Pangolins, order Pholidota, exhibit keratin-derived scales, one of the most iconic skin appendages. This formidable armor is intended to serve as a deterrent against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 95 publications
2
6
0
Order By: Relevance
“…2). This result is consistent with other studies in which a reduction in gene copy number in cetaceans and other groups is associated with evolutionary innovations (Feng et al 2014; Nery et al 2014; Sun et al 2017; Huelsmann et al 2019; Helsen et al 2020a; McGowen et al 2020; Cabrera et al 2021; Randall et al 2022; Zheng et al 2022; Osipova et al 2023; Pinto et al 2023). We annotated, on average, 192.56 ion channels in the genomes of the species included in our taxonomic sampling, representing 0.96% of the protein-coding genes (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2). This result is consistent with other studies in which a reduction in gene copy number in cetaceans and other groups is associated with evolutionary innovations (Feng et al 2014; Nery et al 2014; Sun et al 2017; Huelsmann et al 2019; Helsen et al 2020a; McGowen et al 2020; Cabrera et al 2021; Randall et al 2022; Zheng et al 2022; Osipova et al 2023; Pinto et al 2023). We annotated, on average, 192.56 ion channels in the genomes of the species included in our taxonomic sampling, representing 0.96% of the protein-coding genes (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Taking advantage of the advancement of genomic tools, these adaptations have been investigated from the molecular perspective to expand further our knowledge about the evolutionary process behind the conquest of an aquatic lifestyle (McGowen et al 2011; McGowen et al 2012; Nery, González, et al 2013; Nery, Arroyo, et al 2013; Sun et al 2013; Nery et al 2014; McGowen et al 2020). Interestingly, several studies have reported the loss of genes as a strategy of phenotypic evolution (Feng et al 2014; Nery et al 2014; Sun et al 2017; Huelsmann et al 2019; Helsen et al 2020a; McGowen et al 2020; Randall et al 2022; Zheng et al 2022; Osipova et al 2023; Pinto et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…2020a,b; Haley 2022; Pinto et al. 2023). Hence, it has been speculated that the scales of pangolins serve as a compensatory mechanism for immune deficiency.…”
Section: Adaptive Evolutionmentioning
confidence: 99%
“…Li et al (2020) speculated that the evolution of scales may have helped pangolins better adapt to their living environment, which includes a fair amount of burrowing. Nevertheless, comparative genome analyses have revealed numerous pseudogenization events for skin-related genes, which have caused dysfunction of the sebaceous gland and skin pathogen defense system (Pinto et al 2023). Thus, further research is required to definitively clarify the driving forces behind the evolution of pangolin scales.…”
Section: Scales and Immunitymentioning
confidence: 99%
See 1 more Smart Citation